x=(y+4)*log(2y+3)

Simple and best practice solution for x=(y+4)*log(2y+3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x=(y+4)*log(2y+3) equation:


Simplifying
x = (y + 4) * log(2y + 3)

Reorder the terms:
x = (4 + y) * log(2y + 3)

Reorder the terms:
x = (4 + y) * glo(3 + 2y)

Reorder the terms for easier multiplication:
x = glo(4 + y)(3 + 2y)

Multiply (4 + y) * (3 + 2y)
x = glo(4(3 + 2y) + y(3 + 2y))
x = glo((3 * 4 + 2y * 4) + y(3 + 2y))
x = glo((12 + 8y) + y(3 + 2y))
x = glo(12 + 8y + (3 * y + 2y * y))
x = glo(12 + 8y + (3y + 2y2))

Combine like terms: 8y + 3y = 11y
x = glo(12 + 11y + 2y2)
x = (12 * glo + 11y * glo + 2y2 * glo)
x = (12glo + 11gloy + 2gloy2)

Solving
x = 12glo + 11gloy + 2gloy2

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Simplifying
x = 12glo + 11gloy + 2gloy2

See similar equations:

| 3x^2-8x+3y^2+4=0 | | 216z^3-125y^3= | | B/19-7b/19=54/19 | | 4=x/5=3 | | x/x-2-3/x-1=3/(x-2)(x-1) | | u^2-3u*3u-9= | | 3(63y+42)=84+7(21+42) | | -12-y=98 | | X-.75X=20 | | 2(c+1)+c=44 | | A(2+x)+B(x-1)-1=0 | | x*5=-30 | | 1(x+6)=7 | | 3/5/7/10 | | f(x)=-(x-3)(x+11) | | 18-2[x+(-5)]= | | 6x+5x-4=7 | | V-2.5=1.52 | | 6x-76=64 | | X+4x+2x-4x= | | 3x/7=1-2/5x-10/15 | | 7n+3y+5x=74 | | -2y^2+2y=-2 | | 9w+2=7 | | 5/6dividedby2 | | 3x-10x-5/2=20 | | x=m/4 | | 770/111= | | 2(3x+5)=48 | | y=-4x^3-6 | | -18y+(-2y)+2y= | | 3x-2+y^2=64 |

Equations solver categories